WRITERS’ VOICE AND ENGAGEMENT STRATEGIES IN STUDENTS’ ANALYTICAL EXPOSITION TEXTS - Yuliana, Dian; Gandana, Isti Siti Saleha (Indonesian Journal of Applied Linguistics, 2018)
One criterion of a good analytical exposition lies in the writers’ ability to present a clear position and show their voice in their writing. Such quality can be achieved through skillful use of Engagement resources which allow writers to state their voice by aligning or disaligning it with those of others in presenting their case. Involving nine analytical exposition texts written by university students of different proficiency levels, this study explores how the writers’ voice (Hyland, 2008) is constructed through Engagement resources. Drawing on Martin and White’s Engagement system (Martin White, 2005), the study reveals that, while all of the students are capable of presenting a clear position, students of different proficiency levels indicate different engagement strategies in their writing. Students who are more proficient in English are able to more successfully exploit the resources necessary for constructing a well-argued text and show a stronger sense of authorship. This study is expected to give insights into the use of Engagement resources in developing the writer’s voice in texts written by EFL writer learners in the Indonesian context.